Tinjauan Literatur Tentang Penggunaan Blended Learning Dalam Pembelajaran Pendidikan Agama Islam - yani, suryani; baso, Intan Maharani; Fitri Suci Rahmadani; Adelia Febryanti (South Sulawesi Education Development, 2024)
The purpose of writing this article is to provide an overview of the use of blended learning in the learning process so that it can become a reference in the use of blended learning in PAI learning. The method used in this research is a literature review which uses analyzes from several journals in the last 3 years. The data collection method used is the documentation method. This approach is carried out by analyzing and presenting relevant data selectively according to the referenced literature sources. The results of this study show that using blended learning is effective in learning so that it can improve learning outcomes and student learning independence even though the level of success varies. Therefore, blended learning can be used in learning Islamic religious education.